2014
DOI: 10.4103/0975-5950.154822
|View full text |Cite
|
Sign up to set email alerts
|

Amelogenin in odontogenic cysts and tumors: An immunohistochemical study

Abstract: Background:Amelogenins are the major enamel proteins that play a major role in the biomineralization and structural organization of enamel. Aberrations of enamel-related proteins are thought to be involved in oncogenesis of odontogenic epithelium. The expression of amelogenin is possibly an indicator of differentiation of epithelial cells in the odontogenic lesions.Aims and Objectives:The present study aimed to observe the expression of amelogenin immunohistochemically in various odontogenic lesions.Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…This outcome matched the observations of previous studies [23][24][25][26] In the amyloid deposits of pindborg tumors, ODAM was found as the predominant protein component. 27 It was designated an odontogenic ameloblast-associated protein (ODAM) due to its high expression in enamel-associated epithelia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This outcome matched the observations of previous studies [23][24][25][26] In the amyloid deposits of pindborg tumors, ODAM was found as the predominant protein component. 27 It was designated an odontogenic ameloblast-associated protein (ODAM) due to its high expression in enamel-associated epithelia.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, AMELX is likely an indication of epithelial cell differentiation in odontogenic lesions. This outcome matched the observations of previous studies 23–26 …”
Section: Discussionsupporting
confidence: 91%
“… 21 Currently, has been proposed that the expression of this protein in the odontogenic epithelium would be a potential biomarker of aggressiveness been mild to moderate intensity in ameloblastoma versus teeth germs and absence of this protein in ameloblastic carcinoma. 8 , 20 Furthermore, the possibility of malignant transformation of CEOT is due to dedifferentiation processes or recurrences, which affect the aggressive behavior of this lesion. 29 , 30 , 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 , 6 This protein has been identified in some OCs and OTs. 7 , 8 Amelogenin is secreted by ameloblasts, which are epithelial cells that express different cytokeratins as they differentiate. 9 The expression of multiple cytokeratins in cysts and odontogenic tumors such as CK5/6, 7, 13, 14, 15, 16, 17, 19, AE1/AE3 has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation